MENGOKOHKAN KERANGKA KELUARGA DALAM BINGKAI BIMBINGAN AJARAN ISLAM - Ahmad Masrur Firosad (Jurnal Al-Taujih : Bingkai Bimbingan dan Konseling Islami, 2015)
Life becomes restless, uneasy because of failures in the foster home. That is why the ideal partner of the word family is happy, so ideally be a happy family. Meaning, the goal of every person who is looking for a foster home happiness in life. Almost all of the nation's culture puts family life as a measure of true happiness. Married not too difficult, but building a happy family is not an easy task. Frame buildings (mock) can be discussed and modified in accordance with the concept of mind to be formulated in the form of family building. Likewise, building a happy family, first one must have a concept of a happy family.